Hubungan Indeks Massa Tubuh (IMT) dengan Frekuensi Serangan Asma pada Pasien Asma Wanita yang Menggunakan Kontrasepsi Hormonal dan Tidak - Anggraeni, Aninda Dwi; Harsini, .; Suryawan, Arif (Nexus Kedokteran Klinik, 2014)
Background: Asthma is the most common chronic disease throughout the world which the prevalence of asthma is greater in women. The evidence suggest that sex steroid hormones play an important role in respiratory health. Further, although asthma increased with increasing BMI in all women, this increase was stronger among women taking oral contraception. Therefore, it needs study about correlation BMI with asthma attack frequency in women patient with asthma using hormonal contraception and not. Methods: This study is an observational study with cross sectional conducted in June â July 2014 in Dr. Moewardi general hospital and BBKPM Surakarta. Sampling was done by purposive sampling. Subject to fill (1) bio-data form, (2) Questionnaire. Treatment in respondent (1) Measurement height and weight. Data obtained by 60 subjects and analyzed using Spearman correlation through SPSS 20.00 for Windows. Result: This study shows the value of Spearman correlation r = 0,432; p < 0,05, which means there is a positive correlation was statistically significant between BMI and asthma attack frequency among women taking hormonal contraception with a moderate correlation strength. Whereas among women taking nonhormonal contraception shows the value of Spearman correlation r = 0,363; p < 0,05 which means there is a positive correlation was statistically significant between BMI and asthma attack frequency with a weak correlation strength. Conclusion: There is a moderate positive correlation and statistically significant between BMI and asthma attack frequency among women taking hormonal contraception. And then there is a weak positive correlation and statistically significant between BMI and asthma attack frequency among women taking nonhormonal contraception. Keywords: BMI, Asthma Attack Frequency, ContraceptionÂ